2012
DOI: 10.1101/gr.140269.112
|View full text |Cite
|
Sign up to set email alerts
|

Birth and expression evolution of mammalian microRNA genes

Abstract: MicroRNAs (miRNAs) are major post-transcriptional regulators of gene expression, yet their origins and functional evolution in mammals remain little understood due to the lack of appropriate comparative data. Using RNA sequencing, we have generated extensive and comparable miRNA data for five organs in six species that represent all main mammalian lineages and birds (the evolutionary outgroup) with the aim to unravel the evolution of mammalian miRNAs. Our analyses reveal an overall expansion of miRNA repertoir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
331
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(381 citation statements)
references
References 61 publications
44
331
3
3
Order By: Relevance
“…Before determining a novel miRNA's expression, we made sure to compensate for the sequence depth of the sample at hand: in particular, we used an adaptive thresholding strategy that required a miRNA to be supported by a higher number of sequence reads in samples that were more deeply sequenced. Generally, we found their average expression level to be somewhat lower than that of miRBase miRNAs, in agreement with previous reports (39,(54)(55)(56). We nonetheless stress that all of the novel miRNAs that we discovered are statistically significant (FDR ≤ 0.05) in at least one and typically in many of the analyzed samples: as a matter of fact, 91.5% of the newly discovered miRNAs are statistically significant in 10 or more of the processed samples.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Before determining a novel miRNA's expression, we made sure to compensate for the sequence depth of the sample at hand: in particular, we used an adaptive thresholding strategy that required a miRNA to be supported by a higher number of sequence reads in samples that were more deeply sequenced. Generally, we found their average expression level to be somewhat lower than that of miRBase miRNAs, in agreement with previous reports (39,(54)(55)(56). We nonetheless stress that all of the novel miRNAs that we discovered are statistically significant (FDR ≤ 0.05) in at least one and typically in many of the analyzed samples: as a matter of fact, 91.5% of the newly discovered miRNAs are statistically significant in 10 or more of the processed samples.…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, species-specific miRNAs (e.g., cel-lsy-6 in C. elegans) (62) have also been described and characterized as have been miRNAs that are present only in one or a few species of the same genus. Therefore, enforcing an organism-conservation requirement during miRNA searches is bound to limit the number of potential miRNAs that can be discovered, leaving organism-and lineage-specific miRNAs undiscovered (53)(54)(55)(56). In our effort to further characterize the human miRNA repertoire, we liberated ourselves from the conservation requirement: not surprisingly then, 56.7% of our newly discovered miRNAs are human-specific whereas 94.4% are primate-specific ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all but the amniote study (19) (addressed below), secondary miRNA losses constitute between 27% and 54%, with an overall average of 38%, of the implied evolutionary changes. These phylogenetic results accord well with those of molecular evolutionary studies, in which prevalent secondary loss of miRNA families has been inferred for various taxa (14,(32)(33)(34)(35).…”
Section: Secondary Loss Of Mirna Families Is Commonsupporting
confidence: 89%
“…We tested that these observations were robust to potential biases resulting from differences in miRNA annotation method and sequencing depth in the different species in two ways: first, by repeating the analysis using alternative miRNA sets for human (used for Fig. 4; Meunier et al 2013) and Nematostella miRNAs from miRBase 19 (not shown); and second, by partitioning our Nematostella miRNAs and the miRBase miRNAs by relative abundance level in each species (Supplemental Fig. S4).…”
Section: Comparative Analysis Of Mirna:target Complementaritymentioning
confidence: 99%